2020
DOI: 10.1038/s41598-020-66960-4
|View full text |Cite
|
Sign up to set email alerts
|

Label-free metabolic biomarkers for assessing valve interstitial cell calcific progression

Abstract: Calcific aortic valve disease (CAVD) is the most common form of valve disease where the only available treatment strategy is surgical valve replacement. Technologies for the early detection of CAVD would benefit the development of prevention, mitigation and alternate therapeutic strategies. Two-photon excited fluorescence (TPEF) microscopy is a label-free, non-destructive imaging technique that has been shown to correlate with multiple markers for cellular differentiation and phenotypic changes in cancer and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Our current study is the first instance when a TPEF 755–860 ratio has been shown to demonstrate tissue level changes occurring during early CAVD progression in a mouse model that was more sensitive than the TPEF Col-Cal ratio. Like we had previously demonstrated in our in vitro studies [ 13 , 28 , 52 ], in this study also we observed TPEF autofluorescence ratios decreased at 16 weeks in the pro-calcific mice commissures and correlated with increased calcification, osteogenic differentiation and proliferation. This is also similar to the findings of Quinn et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our current study is the first instance when a TPEF 755–860 ratio has been shown to demonstrate tissue level changes occurring during early CAVD progression in a mouse model that was more sensitive than the TPEF Col-Cal ratio. Like we had previously demonstrated in our in vitro studies [ 13 , 28 , 52 ], in this study also we observed TPEF autofluorescence ratios decreased at 16 weeks in the pro-calcific mice commissures and correlated with increased calcification, osteogenic differentiation and proliferation. This is also similar to the findings of Quinn et al .…”
Section: Discussionsupporting
confidence: 90%
“…We have also shown previously that VICs under pathological stretch have reduced optical redox ratios compared to unstretched cells [ 13 ]. We have also demonstrated that when VICs are subjected to osteogenic conditions in vitro, their optical redox ratio decreased and correlated with gene expression of osteogenic markers like RUNX2, osteopontin and osteocalcin [ 28 ]. In the current study, we measured the TPEF 755–860 ratio (A 860/525 /(A 755/460 + A 860/525 )) from ex vivo tissue sections by obtaining the autofluorescence intensities at 755 nm and 860 nm excitation, which correspond to the NADH and FAD excitation wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has previously reported that when VICs underwent a pathogenic phenotype shift, they experienced a decrease in ORR, suggesting a possible link between VIC pathology and its metabolic state (21,42,43,67). TPEF imaging of VICs under quiescent and osteogenic conditions revealed that the ORR decreased during early osteogenic differentiation (Figure 1F) and correlated with gene expression of osteogenic markers.…”
Section: In Vitro Characterization Of Vic Pathophysiologymentioning
confidence: 71%
“…MPM-based approaches combining TPEF, SHG and CARS, for label-free imaging of an aortic valve have been previously demonstrated (41). TPEF has been used to assess aortic valve interstitial cell (VIC) proliferation (21,42), osteogenesis (43), and valve calcification in vitro and ex vivo (39). TPEF autofluorescence ratios have shown potential in assessing CAVD progression ex vivo (44).…”
Section: Introductionmentioning
confidence: 99%